Nylon composite material as well as preparation method and application thereof
By using amide lubricants modified with fumonisin to improve the compatibility between nylon and glass fiber, the problem of insufficient mechanical properties of nylon composites was solved, and high-strength and high-flow-rate nylon composites were prepared.
Patent Information
- Application Number
- CN202511107283.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-11-18
AI Technical Summary
The poor compatibility between nylon and glass fiber limits the improvement of the mechanical properties of nylon composites, making it difficult to meet the requirements of high-strength applications.
A furfural-modified amide lubricant was used as a modified lubricant and mixed with nylon and long glass fibers. The molecular weight of the lubricant was increased at room temperature through the Diels-Alder reaction, and the chemical bonds were reversibly broken at high temperature, which reduced the melt viscosity of nylon and improved the coating effect of glass fibers.
It improves the compatibility between nylon and glass fiber, enhances the mechanical properties of nylon composites, lowers the production temperature, reduces nylon degradation and yellowing, and enhances the material's flowability and strength.
Smart Images

Figure CN120966236A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials, and in particular to a nylon composite material, its preparation method, and its application. Background Technology
[0002] Nylon (PA), also known as polyamide, is a class of thermoplastic polymers containing repeating amide groups in its molecular chain. It exhibits excellent mechanical properties, hydrophilicity, and abrasion resistance, and is widely used in various industries. For example, Nylon 12 (PA12), chemically known as polydodecanoic acid, is a long-chain, semi-crystalline to crystalline thermoplastic material. PA12 is an excellent electrical insulator with good impact resistance and chemical stability, and is widely used in water meters, cable sheaths, mechanical cams, automotive piping, and athletic shoe soles, among many other applications. However, for applications requiring high strength, PA12's strength and rigidity are slightly insufficient, and glass fiber reinforcement is typically used.
[0003] Long glass fiber reinforced nylon materials have fiber lengths equal to granule lengths, while shorter glass fiber reinforced nylon materials possess high strength, high impact resistance, and good dimensional stability. They can be used as a substitute for steel and reinforcing engineering plastics, meeting the requirements of military, automotive, and home appliance industries. However, the poor compatibility between nylon materials and glass fibers limits the improvement of their mechanical properties and further applications. Summary of the Invention
[0004] Based on this, some embodiments of this application provide a nylon composite material and a method for preparing the same, which can improve the compatibility between glass fiber and nylon and enhance the mechanical properties of the nylon composite material.
[0005] In addition, some other embodiments of this application also provide an application of nylon composite materials.
[0006] A nylon composite material, by weight percentage, comprises: 37%~89% nylon, 10%~60% long glass fiber, and 0.5%~3% modified lubricant;
[0007] The length of the long glass fiber is equal to the length of the nylon composite material, and the modified lubricant includes a furfural-modified amide lubricant.
[0008] In some embodiments, the raw materials for preparing the modified lubricant include: an amide lubricant and a modifier, wherein the amide lubricant includes one or both of erucamide and oleamide, and the modifier includes compounds containing thiol and furfural groups.
[0009] In some embodiments, the modifier includes one or both of 3-mercapto-furfuryl alcohol and furfuryl thiol.
[0010] In some embodiments, the modified lubricant satisfies one or more of the following conditions:
[0011] (1) The molar amount of thiol groups contained in the modifier is 100% to 200% of the molar amount of carbon-carbon double bonds contained in the amide lubricant; optionally, the molar amount of thiol groups contained in the modifier is 120% to 180% of the molar amount of carbon-carbon double bonds contained in the amide lubricant;
[0012] (2) The raw materials for preparing the modified lubricant also include a photoinitiator, and the molar amount of the photoinitiator is 1% to 10% of the molar amount of the modified agent.
[0013] In some embodiments, the molar amount of the photoinitiator is 2% to 6% of the molar amount of the modifier.
[0014] In some embodiments, the photoinitiator includes one or both of 2,2-dimethoxy-2-phenylacetophenone and benzophenone.
[0015] In some embodiments, the nylon includes one or more of nylon 12, nylon 11, and nylon 1012.
[0016] In some embodiments, under test conditions of 190°C and a load of 2.16 kg, the melt index of the nylon is 3 g / 10 min to 40 g / 10 min.
[0017] In some embodiments, the long glass fibers comprise alkali-free long glass fibers.
[0018] In some embodiments, the long glass fiber comprises alkali-free long glass fiber modified with a coupling agent containing amino and / or epoxy groups.
[0019] In some embodiments, one or both of the following conditions are met:
[0020] (1) By weight percentage, the nylon composite material comprises: 50%~78% nylon, 20%~48.5% long glass fiber and 1%~2% modified lubricant;
[0021] (2) The nylon composite material further includes 0.1% to 0.9% antioxidant;
[0022] Optionally, the antioxidant includes one or both of antioxidant 1010 and antioxidant 168.
[0023] A method for preparing a nylon composite material includes the following steps:
[0024] The following raw materials are obtained by weight percentage: 37%~89% nylon, 10%~60% continuous glass fiber, and 0.5%~3% modified lubricant;
[0025] The raw materials are mixed and granulated so that the length of the granules is equal to the length of the continuous glass fibers after shearing, in order to prepare the nylon composite material.
[0026] The modified lubricant includes a furfuryl-modified amide lubricant.
[0027] In some embodiments, the steps of mixing and granulating the raw materials include:
[0028] The nylon and the modified lubricant are mixed to prepare a premix;
[0029] The premix is extruded and then injected into an impregnation mold;
[0030] The continuous glass fiber is fed into the impregnation mold and mixed and impregnated with the premix. After traction and granulation, the nylon composite material is prepared.
[0031] In some embodiments, the step of mixing the raw materials satisfies one or more of the following conditions:
[0032] (1) In the step of mixing the nylon and the modified lubricant, the rotation speed is 50 rpm to 1000 rpm, the temperature is 0℃ to 60℃, and the time is 1 min to 10 min; optionally, the rotation speed is 150 rpm to 600 rpm, the temperature is 15 to 40℃, and the time is 3 min to 6 min.
[0033] (2) In the step of extruding the premix, a twin-screw extruder is used, wherein the screw temperature of the twin-screw extruder is 220℃~300℃ and the rotation speed is 150rpm~900rpm; optionally, the screw temperature is 240℃~280℃ and the rotation speed is 300rpm~700rpm.
[0034] (3) The temperature of the impregnation mold is 260℃~300℃, and optionally, the temperature of the impregnation mold is 270℃~290℃.
[0035] In some embodiments, the modified lubricant is prepared by the following steps:
[0036] An amide lubricant, a modifier, a photoinitiator, and a solvent are mixed, and the amide lubricant is reacted with the modifier under nitrogen protection and ultraviolet light irradiation to prepare the modified lubricant; wherein the amide lubricant includes one or both of erucamide and oleamide, and the modifier includes compounds containing thiol and furfuryl groups.
[0037] In some embodiments, the preparation steps of the modified lubricant satisfy one or more of the following conditions:
[0038] (1) The power of the ultraviolet lamp is 36W~72W and the ultraviolet wavelength is 200nm~360nm; optionally, the ultraviolet wavelength is 250nm~350nm;
[0039] (2) The reaction time between the amide lubricant and the modifier is 10 min to 30 min and the temperature is 10℃ to 40℃; optionally, the reaction time is 15 min to 25 min and the temperature is 20℃ to 35℃.
[0040] Applications of the nylon composite materials described above, or nylon composite materials prepared by the methods described above, in the manufacture of mechanical cams or sports shoe soles.
[0041] Some embodiments of this application include nylon composite materials comprising nylon, long glass fibers, and a modified lubricant in a specific ratio. The modified lubricant includes a furfural-modified amide lubricant. The furfural groups can undergo a reversible chemical and thermal reaction; at room temperature, the furfural groups can undergo a Diels-Alder reaction, increasing the molecular weight of the modified lubricant and preventing a decrease in the mechanical properties of the nylon composite material due to the introduction of small-molecule modified lubricants. Under the high-temperature conditions during the processing and preparation of the nylon composite material, the chemical bonds formed by the furfural reaction are reversibly broken, allowing the modified lubricant to act as a lubricant, reducing the viscosity of the nylon melt, increasing its fluidity, and thus improving the wetting effect of the melt on the long glass fibers, thereby enhancing the mechanical properties of the nylon composite material. Attached Figure Description
[0042] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0043] Figure 1 This is a schematic diagram of a process flow for preparing nylon composite materials according to some embodiments of this application. Detailed Implementation
[0044] To facilitate understanding of this application, a more comprehensive description of the application will be provided below in conjunction with specific embodiments. Preferred embodiments of the application are given in the specific embodiments. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application.
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein in the specification of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0046] Unless otherwise stated or in case of conflict, the terms or phrases used in this application shall have the following meanings:
[0047] In this application, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" and "second" may explicitly or implicitly include at least one of those features.
[0048] In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise expressly and specifically limited.
[0049] In this application, "one or more" refers to any one, two, or more of the listed items. "Multiple" refers to any two or more of the listed items.
[0050] Unless otherwise specified, all percentage concentrations mentioned in this application refer to the final concentration. The final concentration refers to the proportion of the added component in the system after the addition of that component.
[0051] In this application, terms such as "further," "even more," "particularly," "for example," "like," "example," and "exemplary" are used for descriptive purposes to indicate a connection in the coverage of different technical solutions presented earlier and later, but should not be construed as limiting the preceding technical solution or restricting the scope of protection herein. Unless otherwise specified herein, A (e.g., B) indicates that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0052] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it is selected from either "present" or "absent." If multiple "options" appear in a technical solution, unless otherwise specified and there are no contradictions or mutual constraints, each "option" is independent. In this application, descriptions such as "optionally contains" and "optionally includes" indicate "contains or does not contain." "Optional component X" indicates whether component X exists or does not exist, or whether component X is contained or not.
[0053] When a numerical range is disclosed in this application, the range is considered continuous and includes the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to an integer, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed in this application should be understood to include any and all subranges to which they are included.
[0054] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0055] The terms "comprising" and "having," and any variations thereof, used in the embodiments of this application, are intended to cover non-exclusive inclusion. For example, a process, method, system, product, or device that includes a series of steps or units is not limited to the steps or units listed, but may optionally include steps or units not listed, or may optionally include other steps or components inherent to such processes, methods, products, or devices.
[0056] In this application, the reference to "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a mutually exclusive, independent, or alternative embodiment. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described in this application can be combined with other embodiments.
[0057] In the flowchart of this application, although the steps are shown sequentially according to the arrows, these steps are not necessarily performed in the order indicated by the arrows. Unless otherwise specified herein, there is no strict order restriction on the execution of these steps. They can be executed in other orders. Moreover, at least some of the steps in the diagram may include multiple sub-steps or multiple stages. These sub-steps or stages are not necessarily completed at the same time, but can be executed at different times. Their execution order is not necessarily sequential, but can be performed alternately or in turn with at least some of other steps or other sub-steps or stages.
[0058] Unless otherwise specified, "%" in this application refers to the percentage of mass "wt%".
[0059] Alkali-free long glass fiber refers to long glass fiber with an alkali metal oxide content of ≤0.5%, usually in the form of aluminum borosilicate system, which has excellent mechanical properties and electrical insulation.
[0060] As described in the background section, in traditional long glass fiber reinforced nylon composites, the compatibility between nylon and long glass fibers is poor. Although related technologies have produced long glass fiber reinforced nylon materials, they have not improved the compatibility problem between nylon and long glass fibers, and the mechanical properties need to be improved. Based on this, some embodiments of this application provide a nylon composite material and a method for preparing the same.
[0061] The first aspect of this application provides a nylon composite material, which, by weight percentage, comprises: 37%~89% nylon, 10%~60% long glass fiber, and 0.5%~3% modified lubricant;
[0062] The length of the long glass fiber is equal to the length of the nylon composite material, and the modified lubricant includes a furfural-modified amide lubricant.
[0063] Some embodiments of this application include nylon composite materials comprising nylon, long glass fibers, and a modified lubricant in a specific ratio. The modified lubricant includes a furfural-modified amide lubricant. The furfural group can undergo a reversible chemical and thermal reaction; at room temperature, the furfural groups can undergo a Diels-Alder reaction to increase the molecular weight of the modified lubricant, thus preventing a decrease in the mechanical properties of the nylon composite material due to the introduction of small-molecule modified lubricants. Under the high-temperature conditions during the processing and preparation of the nylon composite material, the chemical bonds formed by the furfural reaction are reversibly broken, allowing the modified lubricant to act as a lubricant, reducing the viscosity of the nylon melt, increasing its fluidity, and thereby improving the wetting effect of the melt on the long glass fibers, ultimately enhancing the mechanical properties of the nylon composite material.
[0064] Specifically, the Diels-Adel reaction involves the cyclic 1,4-addition between conjugated double bonds and compounds containing double bonds to form cyclic compounds. Furfuryl has a conjugated diene structure, with one molecule acting as a conjugated double bond and the other molecule being a compound containing double bonds. The two can undergo dimerization at room temperature to generate cyclic compounds, and can undergo dedimerization at high temperatures, breaking the chemical bonds. This allows furfuryl-modified amide lubricants to react at room temperature to increase the molecular weight of the lubricant, and to reversibly break the chemical bonds at high temperatures, thus acting as a lubricant and improving melt fluidity.
[0065] Furthermore, the introduction of modified lubricants can lower the production temperature, reducing nylon degradation and yellowing caused by high temperatures.
[0066] In some embodiments, the nylon includes one or more of nylon 12, nylon 11, and nylon 1012. Using the above-mentioned nylons results in better compatibility with modified lubricants, which is beneficial for further improving the mechanical properties of nylon composite materials.
[0067] In some embodiments, under test conditions of 190°C and a load of 2.16 kg, the melt index of nylon is 3 g / 10 min to 40 g / 10 min. For example, the melt index of nylon may be, but is not limited to, 3 g / 10 min, 5 g / 10 min, 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min, or a range of any two of these values.
[0068] In some embodiments, the mass percentage of nylon in the nylon composite material is 37% to 89%. For example, the mass percentage of nylon in the nylon composite material may be, but is not limited to, 37%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, 72%, 75%, 78%, 80%, 82%, 85%, 89%, or any range of two of these values. Optionally, the mass percentage of nylon in the nylon composite material is 50% to 78%.
[0069] In some embodiments, the long glass fibers include alkali-free long glass fibers.
[0070] In some embodiments, the long glass fibers comprise alkali-free long glass fibers modified with a coupling agent containing amino and / or epoxy groups. Using these long glass fibers, the amino and / or epoxy groups can adsorb onto the nylon material through polar interactions or hydrogen bonding, improving the interfacial bonding between the glass fibers and nylon. Furthermore, the coupling agent modification can reduce the surface energy of the glass fibers, improve their dispersibility, and reduce fiber agglomeration.
[0071] In some embodiments, the mass percentage of long glass fibers in the nylon composite material is 10% to 60%. For example, the mass percentage of long glass fibers in the nylon composite material may be, but is not limited to, 10%, 15%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 55%, 60%, or any range of two of these values. Optionally, the mass percentage of long glass fibers in the nylon composite material is 20% to 48.5%.
[0072] In some embodiments, the length of the nylon composite material is 6 mm to 16 mm. For example, the length of the nylon composite material may be, but is not limited to, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 12 mm, 14 mm, 16 mm, or any combination of these values.
[0073] In some embodiments, the raw materials for preparing the modified lubricant include: an amide lubricant and a modifier, wherein the amide lubricant includes one or both of erucamide and oleamide, and the modifier includes compounds containing thiol and furfural groups.
[0074] In some embodiments, the modifier includes one or both of 3-mercapto-furfuryl alcohol and furfuryl thiol.
[0075] In some embodiments, the molar amount of thiol groups in the modifier is 100% to 200% of the molar amount of carbon-carbon double bonds in the amide lubricant. For example, the molar amount of thiol groups in the modifier is 100%, 110%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, 190%, 200% of the molar amount of carbon-carbon double bonds in the amide lubricant, or a range consisting of any two of these values. Optionally, the molar amount of thiol groups in the modifier is 120% to 180% of the molar amount of carbon-carbon double bonds in the amide lubricant.
[0076] Modified lubricants are prepared using amide lubricants and modifiers. These modified lubricants function as lubricants at high temperatures, reducing the viscosity of the nylon melt, improving the coating effect of the melt on long glass fibers, and thus increasing the strength of the nylon composite material. The introduction of lubricants can lower the production temperature, reducing nylon degradation and yellowing caused by high temperatures. The modified lubricants undergo a chemical reaction at room temperature, increasing their molecular weight and preventing the introduction of small-molecule lubricants from reducing the mechanical properties of the product.
[0077] In some embodiments, the raw materials for preparing the modified lubricant further include a photoinitiator, the molar amount of which is 1% to 10% of the molar amount of the modifier. For example, the molar amount of the photoinitiator is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% of the molar amount of the modifier, or any range of two of these values. Optionally, the molar amount of the photoinitiator is 2% to 6% of the molar amount of the modifier.
[0078] In some embodiments, the photoinitiator includes one or both of 2,2-dimethoxy-2-phenylacetophenone (DMPA) and benzophenone.
[0079] In some embodiments, the modified lubricant has a mass percentage of 0.5% to 3% in the nylon composite material. For example, the mass percentage of the modified lubricant in the nylon composite material may be, but is not limited to, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any combination of these values.
[0080] In some embodiments, the raw materials for preparing the nylon composite material, by weight percentage, include: 37% to 89% nylon, 10% to 60% continuous glass fiber, and 0.5% to 3% modified lubricant. That is, during the preparation of the nylon composite material, the continuous glass fiber is cut into long glass fibers of the same length as the nylon composite material granules.
[0081] In some embodiments, the nylon composite material comprises, by weight percentage: 50%~78% nylon, 20%~48.5% long glass fiber, and 1%~2% modified lubricant. Specifically, the raw materials for preparing the nylon composite material comprise, by weight percentage: 50%~78% nylon, 20%~48.5% continuous glass fiber, and 1%~2% modified lubricant.
[0082] In some embodiments, the nylon composite material further includes 0.1% to 0.9% antioxidant. For example, the mass percentage of antioxidant in the nylon composite material may be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, or any combination of these values.
[0083] Specifically, the antioxidant can be a commercially available nylon antioxidant commonly used in the art. In some embodiments, the antioxidant includes one or both of antioxidant 1010 and antioxidant 168.
[0084] In some embodiments, the nylon composite material comprises: 37% to 89% nylon, 10% to 60% long glass fiber, 0.5% to 3% modified lubricant, and 0.1% to 0.9% antioxidant.
[0085] In other embodiments, the nylon composite material comprises: 50%~78%, long glass fibers 20%~48.5%, modified lubricant 1%~2%, and antioxidant 0.1%~0.9%.
[0086] The second aspect of this application provides a method for preparing a nylon composite material; please refer to [link to relevant documentation]. Figure 1 It includes the following steps:
[0087] Step S110: Obtain the following raw materials by mass percentage: 37%~89% nylon, 10%~60% continuous glass fiber and 0.5%~3% modified lubricant.
[0088] Step S120: Mix and granulate the raw materials to make the length of the granules equal to the length of the continuous glass fibers after shearing, and prepare nylon composite materials.
[0089] Among them, modified lubricants include furfury-modified amide lubricants.
[0090] The specific raw materials used in the preparation are the same as those in the first aspect mentioned above, and will not be repeated here.
[0091] In some embodiments, the modified lubricant is prepared by the following steps:
[0092] A modified lubricant is prepared by mixing an amide lubricant, a modifier, a photoinitiator, and a solvent, and reacting the amide lubricant with the modifier under nitrogen protection and ultraviolet light irradiation. The amide lubricant includes one or both of erucamide and oleamide, and the modifier includes compounds containing mercapto and furfuryl groups.
[0093] In some embodiments, the molar amount of thiol groups in the modifier is 100% to 200% of the molar amount of carbon-carbon double bonds in the amide lubricant. Optionally, the molar amount of thiol groups in the modifier is 120% to 180% of the molar amount of carbon-carbon double bonds in the amide lubricant.
[0094] In some embodiments, the molar amount of the photoinitiator is 1% to 10% of the molar amount of the modifier. Optionally, the molar amount of the photoinitiator is 2% to 6% of the molar amount of the modifier.
[0095] In some embodiments, the mass of the solvent is 10 to 80 times the total mass of the amide lubricant, modifier, and photoinitiator. Optionally, the mass of the solvent is 20 to 60 times the total mass of the amide lubricant, modifier, and photoinitiator.
[0096] In some of these embodiments, the solvent includes N,N-dimethylformamide (DMF).
[0097] In some embodiments, the ultraviolet lamp has a power of 36W to 72W and an ultraviolet wavelength of 200nm to 360nm. Optionally, the ultraviolet wavelength is 250nm to 350nm.
[0098] In some embodiments, the reaction time between the amide lubricant and the modifier is 10 min to 30 min, and the temperature is 10°C to 40°C. Optionally, the reaction time between the amide lubricant and the modifier is 15 min to 25 min, and the temperature is 20°C to 35°C.
[0099] In some embodiments, the rotation speed is 50 rpm to 200 rpm during the step of reacting the amide lubricant with the modifier. Optionally, the rotation speed is 60 rpm to 150 rpm.
[0100] In some embodiments, the step of mixing the amide lubricant, modifier, photoinitiator, and solvent, and reacting the amide lubricant with the modifier under nitrogen protection and ultraviolet light irradiation includes:
[0101] Mix and stir the amide lubricant, modifier, photoinitiator and solvent. After all components are dissolved, purge with nitrogen to replace the air.
[0102] While stirring, turn on the ultraviolet lamp to irradiate the mixture, allowing the amide lubricant and modifier to react.
[0103] Specifically, in the step of mixing and stirring the amide lubricant, modifier, photoinitiator, and solvent, the stirring temperature is 10℃~40℃ and the stirring speed is 50rpm~200rpm. Optionally, the stirring temperature is 20℃~35℃ and the stirring speed is 60rpm~150rpm.
[0104] Specifically, the nitrogen gas replaces the air for 3 to 5 minutes.
[0105] In some embodiments, the reaction is further complicated by steps of solvent removal, washing, filtration and drying.
[0106] Specifically, the solvent is removed by rotary evaporation. In one example, the rotary evaporation temperature is 50℃~120℃, optionally 70℃~100℃. In one example, the rotary evaporation vacuum degree is -0.1MPa~-0.03MPa, optionally -0.08MPa~-0.05MPa. In one example, the rotary evaporation time is 3h~8h, optionally 4h~6h.
[0107] Specifically, in the washing step, anhydrous ethanol is used for washing. In one example, the amount of anhydrous ethanol used is 3 to 10 times the mass of the sample after solvent removal; alternatively, the amount of anhydrous ethanol used is 5 to 8 times the mass of the sample after solvent removal.
[0108] Specifically, in the filtration process, the vacuum level is -0.03MPa to -0.01MPa, and the temperature is 10℃ to 35℃.
[0109] Specifically, in the drying step, the temperature is 50℃~80℃, optionally, the drying temperature is 60℃~75℃. Specifically, the drying time is 3h~8h, optionally, the drying time is 4h~6h.
[0110] In some embodiments, the steps of mixing and granulating the raw materials include:
[0111] A premix was prepared by mixing nylon and a modified lubricant.
[0112] The premix is extruded and then injected into the impregnation mold;
[0113] Continuous glass fibers are fed into an impregnation mold, mixed and impregnated with a premix, and then drawn and granulated to obtain a nylon composite material.
[0114] After continuous glass fibers and molten nylon are fully impregnated in an impregnation mold using the above process, they are then drawn and granulated into particles of different lengths. The final length of the nylon composite material is equal to the length of the sheared glass fibers, meaning that the continuous glass fibers are cut into long glass fibers of the same length as the granules during the preparation process.
[0115] In some embodiments, the mixing step of nylon and modified lubricant is performed at a rotation speed of 50 rpm to 1000 rpm, a temperature of 0°C to 60°C, and a time of 1 min to 10 min. Optionally, the mixing step of nylon and modified lubricant is performed at a rotation speed of 150 rpm to 600 rpm, a temperature of 15°C to 40°C, and a time of 3 min to 6 min.
[0116] In one example, an antioxidant was also added during the step of mixing nylon and modified lubricant.
[0117] In some embodiments, the extrusion step of the premix is performed using a twin-screw extruder with a screw temperature of 220°C to 300°C and a rotation speed of 150 rpm to 900 rpm. Optionally, the screw temperature is 240°C to 280°C and the rotation speed is 300 rpm to 700 rpm.
[0118] In one example, the premix is added through the main feed port of a twin-screw extruder.
[0119] In some embodiments, the temperature of the impregnation mold is 260°C to 300°C. Optionally, the temperature is 270°C to 290°C.
[0120] In one example, continuous glass fibers are added to the impregnation mold via a fiber feeding rack and a fiber spreading rack.
[0121] The process involves mixing nylon, modified lubricant, and optionally antioxidant, extruding the mixture through a twin-screw extruder, and then injecting it into an impregnation die. This allows the continuous glass fibers to be mixed and impregnated with the premix in the impregnation die, which helps the nylon to fully penetrate and coat the continuous glass fibers, thus improving the impregnation effect.
[0122] This application discloses a method for preparing nylon composite materials using nylon, continuous glass fibers, and a modified lubricant as raw materials. The process involves extrusion, impregnation, traction, and granulation. The continuous glass fibers are fully impregnated with molten nylon in an impregnation mold and then cut into granules, transforming the continuous glass fibers into long glass fibers of the same length as the granules. During the preparation process, the modified lubricant acts as a lubricant at high temperatures, reducing the viscosity of the nylon melt and improving the coating effect of the melt on the continuous glass fibers, thereby increasing the strength of the composite material. Furthermore, because the modified lubricant contains furfural, it reacts at room temperature, increasing its molecular weight and preventing a decrease in the mechanical properties of the product due to its introduction. In addition, the introduction of the modified lubricant can lower the production temperature, reducing nylon degradation and yellowing caused by high temperatures.
[0123] The preparation methods of nylon composite materials in some embodiments of this application are simple and can obtain nylon composite materials with good compatibility and excellent mechanical properties.
[0124] A third aspect of this application provides the use of a nylon composite material in the manufacture of mechanical cams or athletic shoe soles.
[0125] The aforementioned nylon composite material possesses excellent mechanical properties and can be used in the manufacture of mechanical cams or athletic shoe soles.
[0126] To make the objectives and advantages of this application clearer, the following detailed description of the nylon composite material and its effects, in conjunction with specific embodiments, is provided. It should be understood that the specific embodiments described herein are for illustrative purposes only and should not be construed as limiting the scope of this application. Unless otherwise specified, the following embodiments do not include components other than unavoidable impurities. Unless otherwise specified, the drugs and instruments used in the embodiments are conventionally selected in the art. Experimental methods not specifying specific conditions in the embodiments were implemented under conventional conditions, such as those described in literature, books, or methods recommended by the manufacturer.
[0127] The raw material information used in the examples and comparative examples is shown in Table 1 below.
[0128] Table 1
[0129]
[0130] The supplier of the equipment used to prepare the nylon composite material was Nanjing Chuangbo, model TSH-40-900-75-40.
[0131] The mixing machine used: 120L mixing machine, Dongguan Ruiside.
[0132] The tensile strength in the examples and comparative examples was tested according to standard ISO 527, with a specimen size of 130mm × 10mm × 0.8mm and a tensile rate of 50mm / min; the flexural strength / modulus was tested according to standard ISO 178, with a specimen size of 130mm × 10mm × 0.8mm; and the impact strength was tested according to standard ISO 180 (notched, 23°C), with a specimen size of 130mm × 10mm × 0.8mm.
[0133] Example 1
[0134] This embodiment provides a nylon composite material, the raw materials of which, by mass percentage, include: 68.6% nylon 12PA12-1, 30% continuous glass fiber 4301R, 1% modified lubricant, 0.2% antioxidant 1010 and 0.2% antioxidant 168.
[0135] The modified lubricant is prepared through the following steps:
[0136] The lubricant erucamide, the modifier 3-mercapto-furfuryl alcohol, the photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA), and the solvent DMF were mixed and stirred in a flask. The molar amount of thiol groups in the modifier was 150% of the molar amount of carbon-carbon double bonds in the lubricant, and the molar amount of the photoinitiator was 4% of the molar amount of the modifier. The mass of the solvent was 50 times the total mass of the lubricant, modifier, and photoinitiator. The stirring temperature was 30℃, and the stirring speed was 120 rpm. After all substances were completely dissolved, nitrogen gas was introduced to replace the air in the flask for 4 minutes. Plastic wrap was placed between the flask mouth and the tetrafluoroethylene stopper. The mixture was stirred continuously, and the flask was irradiated with a 36W UV lamp at a wavelength of 300 nm at 30℃ for 20 minutes. The stirring speed was 80 rpm. After the reaction was completed, the sample was vacuum-dried at 90℃ and -0.07MPa for 5 hours. The dried sample was then washed with anhydrous ethanol, the amount of which was 6 times the mass of the material after vacuum-drying. The sample was then filtered at -0.02MPa and 25℃. After filtration, the sample was dried at 70℃ for 5 hours to obtain the modified lubricant.
[0137] The preparation method of the nylon composite material in this embodiment includes the following steps:
[0138] (1) Nylon 12, modified lubricant and antioxidant are mixed in a mixer at a ratio of 400 rpm, 30°C, and 5 min to obtain a premix.
[0139] (2) The above premix is added through the main feed port of the twin-screw extruder and enters the melt-impregnated glass fiber mold after passing through the twin-screw extruder. The screw temperatures of the twin-screw extruder are 240℃, 280℃, 290℃, 300℃, 300℃, 290℃, 290℃, 280℃, 280℃, 280℃, and 280℃, and the rotation speed is 500 rpm.
[0140] (3) Continuous glass fibers are added to the melt impregnation glass fiber mold through the fiber feeding frame and the fiber spreading frame. The temperature of the melt impregnation glass fiber mold is 260℃, 280℃, 290℃ and 290℃ respectively. By traction and granulation, the length of the granules is equal to the length of the continuous glass fibers after shearing, and the nylon composite material of this embodiment is obtained.
[0141] After the nylon composite material prepared above was processed into a sample, its performance was tested according to the standard. The test results are shown in Table 2.
[0142] Example 2
[0143] This embodiment provides a nylon composite material, the raw materials of which, by mass percentage, include: 88.3% nylon 12 (PA12-2), 11% continuous glass fiber 4301H, 0.5% modified lubricant, 0.1% antioxidant 1010 and 0.1% antioxidant 168.
[0144] The modified lubricant is prepared through the following steps:
[0145] The lubricant oleamide, the modifier furfuryl mercaptan, the photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA), and the solvent DMF were mixed and stirred in a flask. The molar amount of mercapto groups in the modifier was 100% of the molar amount of carbon-carbon double bonds in the lubricant, the molar amount of the photoinitiator was 1% of the molar amount of the modifier, and the mass of the solvent was 10 times the total mass of the lubricant, modifier, and photoinitiator. The stirring temperature was 10℃, and the stirring speed was 50 rpm. After all substances were completely dissolved, nitrogen gas was introduced to replace the air in the flask for 3 minutes. Plastic wrap was placed between the flask mouth and the tetrafluoroethylene stopper. While maintaining stirring, the flask was irradiated with a 36W UV lamp (200nm wavelength) for 10 minutes at 10℃ and a stirring speed of 50 rpm. After the reaction was complete, the mixture was vacuum-dried at 50℃ and a vacuum of -0.03 MPa for 4 hours. After drying, anhydrous ethanol was added to the dried sample for washing. The amount of ethanol was three times the mass of the material after rotary evaporation. After washing, the sample was filtered under a vacuum of -0.01 MPa and a temperature of 10°C. After filtration, the sample was dried at 50°C for 3 hours to obtain the modified lubricant.
[0146] The preparation method of the nylon composite material in this embodiment includes the following steps:
[0147] (1) Nylon 12, modified lubricant and antioxidant are mixed in a mixer at a ratio of 1000 rpm, 5℃, and 1 min to obtain a premix.
[0148] (2) The above premix is added through the main feed port of the twin-screw extruder and enters the melt-impregnated glass fiber mold after passing through the twin-screw extruder. The screw temperatures of the twin-screw extruder are 240℃, 280℃, 300℃, 300℃, 290℃, 290℃, 290℃, 280℃, 280℃, 270℃, and 270℃, and the rotation speed is 900 rpm.
[0149] (3) Continuous glass fibers are added to the melt impregnation glass fiber mold through the fiber feeding frame and the fiber spreading frame. The temperature of the melt impregnation glass fiber mold is 270℃, 280℃, 290℃ and 300℃ respectively. By traction and granulation, the length of the granules is equal to the length of the continuous glass fibers after shearing, and the nylon composite material of this embodiment is obtained.
[0150] After the nylon composite material prepared above was processed into a sample, its performance was tested according to the standard. The test results are shown in Table 2.
[0151] Example 3
[0152] This embodiment provides a nylon composite material, the raw materials of which, by mass percentage, include: 77.8% nylon 12 (PA12-1), 21% continuous glass fiber 4301R, 0.6% modified lubricant, 0.3% antioxidant 1010 and 0.3% antioxidant 168.
[0153] The modified lubricant is prepared through the following steps:
[0154] The lubricant erucamide, modifier 3-mercapto-furfuryl alcohol, photoinitiator benzophenone, and solvent DMF were mixed and stirred in a flask. The molar amount of thiol groups in the modifier was 200% of the molar amount of carbon-carbon double bonds in the lubricant, the molar amount of the photoinitiator was 10% of the molar amount of the modifier, and the mass of the solvent was 80 times the total mass of the lubricant, modifier, and light stabilizer. The stirring temperature was 40℃, and the stirring speed was 200 rpm. After all substances were completely dissolved, nitrogen gas was introduced to replace the air in the beaker for 5 minutes. Plastic wrap was placed between the flask mouth and the PTFE stopper. While maintaining stirring, the flask was irradiated with a 36W UV lamp (360nm wavelength) at 40℃ and the stirring speed was 200 rpm for 30 minutes. After the reaction was complete, the mixture was vacuum-dried at 120℃ and a vacuum of -0.1 MPa for 7 hours. After drying, anhydrous ethanol was added to the dried sample for washing. The amount of anhydrous ethanol was 10 times the mass of the material after rotary evaporation. After washing, the sample was filtered under a vacuum of -0.03 MPa and a temperature of 35°C. After filtration, the sample was dried at 80°C for 8 hours to obtain the modified lubricant.
[0155] The preparation method of the nylon composite material in this embodiment includes the following steps:
[0156] (1) Nylon 12, modified lubricant and antioxidant are mixed in a mixer at a ratio of 600 rpm, 55°C, and 3 min to obtain a premix.
[0157] (2) The above premix is added through the main feed port of the twin-screw extruder and enters the melt-impregnated glass fiber mold after passing through the twin-screw extruder. The screw temperatures of the twin-screw extruder are 240℃, 280℃, 300℃, 300℃, 290℃, 290℃, 290℃, 280℃, 280℃, 280℃, and 270℃, and the rotation speed is 800 rpm.
[0158] (2) Continuous glass fibers are added to the melt impregnation glass fiber mold through the fiber feeding frame and the fiber spreading frame. The temperature of the melt impregnation glass fiber mold is 280℃, 280℃, 300℃ and 300℃ respectively. By traction and granulation, the length of the granules is equal to the length of the continuous glass fibers after shearing, and the nylon composite material of this embodiment is obtained.
[0159] After the above-mentioned nylon composite material was processed into a sample, its performance was tested according to the standard. The test results are shown in Table 2.
[0160] Example 4
[0161] This embodiment provides a nylon composite material, the raw materials of which, by mass percentage, include: 47.8% nylon 12 (PA12-1), 50% continuous glass fiber 4301H, 1.5% modified lubricant, 0.3% antioxidant 1010 and 0.4% antioxidant 168.
[0162] The modified lubricant is prepared through the following steps:
[0163] The lubricant oleamide, modifier 3-mercapto-furfuryl alcohol, photoinitiator benzophenone, and solvent DMF were mixed and stirred in a flask. The molar amount of thiol groups in the modifier was 120% of the molar amount of carbon-carbon double bonds in the lubricant, the molar amount of the photoinitiator was 2% of the molar amount of the modifier, and the mass of the solvent was 20 times the total mass of the lubricant, modifier, and photoinitiator. The stirring temperature was 20℃, and the stirring speed was 60 rpm. After all substances were completely dissolved, nitrogen gas was introduced to replace the air in the beaker for 4 minutes. Plastic wrap was placed between the flask mouth and the PTFE stopper. While maintaining stirring, the flask was irradiated with a 36W UV lamp (250nm wavelength) for 15 minutes at 20℃ and a stirring speed of 60 rpm. After the reaction was complete, the mixture was vacuum-dried at 70℃ and a vacuum degree of -0.05 MPa for 5 hours. After drying, anhydrous ethanol was added to the dried sample for washing. The amount of anhydrous ethanol used was five times the mass of the material after rotary evaporation. After washing, the sample was filtered under a vacuum of -0.02 MPa at a temperature of 25°C. After filtration, the sample was dried at 60°C for 4 hours to obtain the modified lubricant.
[0164] The preparation method of the nylon composite material in this embodiment includes the following steps:
[0165] (1) Nylon 12, modified lubricant and antioxidant are mixed in a mixer at a ratio of 150 rpm, 15℃, and 6 min to obtain a premix.
[0166] (2) The above premix is added through the main feed port of the twin-screw extruder and enters the melt-impregnated glass fiber mold after passing through the twin-screw extruder. The screw temperatures of the twin-screw extruder are 250℃, 280℃, 300℃, 300℃, 290℃, 290℃, 290℃, 280℃, 280℃, and 280℃, and the rotation speed is 300 rpm.
[0167] (3) Continuous glass fibers are added to the melt impregnation glass fiber mold through the fiber feeding frame and the fiber spreading frame. The temperature of the melt impregnation glass fiber mold is 280℃, 290℃, 300℃ and 300℃ respectively. By traction and granulation, the length of the granules is equal to the length of the continuous glass fibers after shearing, and the nylon composite material of this embodiment is obtained.
[0168] After the nylon composite material of this embodiment was processed into a sample, its performance was tested according to the standard. The test results are shown in Table 2.
[0169] Example 5
[0170] This embodiment provides a nylon composite material, the raw materials of which, by mass percentage, include: 37.1% nylon 12 (PA12-2), 60% continuous glass fiber 4301R, 2% modified lubricant, 0.5% antioxidant 1010 and 0.4% antioxidant 168.
[0171] The modified lubricant is prepared through the following steps:
[0172] The lubricant erucamide, the modifier furfuryl mercaptan, the photoinitiator benzophenone, and the solvent DMF were mixed and stirred in a flask. The molar amount of thiol groups in the modifier was 180% of the molar amount of carbon-carbon double bonds in the lubricant, the molar amount of the photoinitiator was 6% of the molar amount of the modifier, and the mass of the solvent was 60 times the total mass of the lubricant, modifier, and photoinitiator. The stirring temperature was 35℃, and the stirring speed was 150 rpm. After all substances were completely dissolved, nitrogen gas was introduced to replace the air in the beaker for 5 minutes. Plastic wrap was placed between the flask mouth and the PTFE stopper. While maintaining stirring, the flask was irradiated with a 36W UV lamp (350nm wavelength) for 25 minutes at 35℃ and a stirring speed of 150 rpm. After the reaction was complete, the mixture was vacuum-dried at 100℃ and a vacuum of -0.08 MPa for 6 hours. After drying, anhydrous ethanol was added to the dried sample for washing, with the amount of anhydrous ethanol being 8 times the mass of the sample after rotary evaporation drying. After washing, the sample was filtered under a vacuum of -0.03 MPa at 35°C. After filtration, the sample was dried at 75°C for 6 hours to obtain the modified lubricant.
[0173] The preparation method of the nylon composite material in this embodiment includes the following steps:
[0174] (1) Nylon 12, modified lubricant and antioxidant are mixed in a mixer at a ratio of 50 rpm, 40 ℃, and 10 min to obtain a premix.
[0175] (2) The above premix is added through the main feed port of the twin-screw extruder and enters the melt-impregnated glass fiber mold after passing through the twin-screw extruder. The screw temperatures of the twin-screw extruder are 250℃, 280℃, 300℃, 300℃, 290℃, 290℃, 290℃, 290℃, 280℃, and 280℃, and the rotation speed is 150 rpm.
[0176] (3) Continuous glass fibers are added to the melt impregnation glass fiber mold through the fiber feeding frame and the fiber spreading frame. The temperature of the melt impregnation glass fiber mold is 290℃, 290℃, 300℃ and 300℃ respectively. By traction and granulation, the length of the granules is equal to the length of the continuous glass fibers after shearing, and the nylon composite material of this embodiment is obtained.
[0177] After the nylon composite material of this embodiment was processed into a sample, its performance was tested according to the standard. The test results are shown in Table 2.
[0178] Example 6
[0179] This embodiment provides a nylon composite material, the raw materials of which, by mass percentage, include: 68.6% nylon 11PA11, 30% continuous glass fiber 4301R, 1% modified lubricant, 0.2% antioxidant 1010 and 0.2% antioxidant 168.
[0180] The modified lubricant is prepared through the following steps:
[0181] The lubricant erucamide, the modifier 3-mercapto-furfuryl alcohol, the photoinitiator 2,2-dimethoxy-2-phenylacetophenone (DMPA), and the solvent DMF were mixed and stirred in a flask. The molar amount of thiol groups in the modifier was 150% of the molar amount of carbon-carbon double bonds in the lubricant, and the molar amount of the photoinitiator was 4% of the molar amount of the modifier. The mass of the solvent was 50 times the total mass of the lubricant, modifier, and photoinitiator. The stirring temperature was 30℃, and the stirring speed was 120 rpm. After all substances were completely dissolved, nitrogen gas was introduced to replace the air in the flask for 4 minutes. Plastic wrap was placed between the flask mouth and the tetrafluoroethylene stopper. The mixture was stirred continuously, and the flask was irradiated with a 36W UV lamp at a wavelength of 300 nm at 30℃ for 20 minutes. The stirring speed was 80 rpm. After the reaction was completed, the sample was vacuum-dried at 90℃ and -0.07MPa for 5 hours. The dried sample was then washed with anhydrous ethanol, the amount of which was 6 times the mass of the material after vacuum-drying. The sample was then filtered at -0.02MPa and 25℃. After filtration, the sample was dried at 70℃ for 5 hours to obtain the modified lubricant.
[0182] The preparation method of the nylon composite material in this embodiment includes the following steps:
[0183] (1) Nylon 11, modified lubricant and antioxidant are mixed in a mixer at a ratio of 400 rpm, 30°C, and 5 min to obtain a premix.
[0184] (2) The above premix is added through the main feed port of the twin-screw extruder and enters the melt-impregnated glass fiber mold after passing through the twin-screw extruder. The screw temperatures of the twin-screw extruder are 240℃, 280℃, 290℃, 300℃, 300℃, 290℃, 290℃, 280℃, 280℃, 280℃, and 280℃, and the rotation speed is 500 rpm.
[0185] (3) Continuous glass fibers are added to the melt impregnation glass fiber mold through the fiber feeding frame and the fiber spreading frame. The temperature of the melt impregnation glass fiber mold is 260℃, 280℃, 290℃ and 290℃ respectively. By traction and granulation, the length of the granules is equal to the length of the continuous glass fibers after shearing, and the nylon composite material of this embodiment is obtained.
[0186] After the nylon composite material prepared above was processed into a sample, its performance was tested according to the standard. The test results are shown in Table 2.
[0187] Comparative Example 1
[0188] Comparative Example 1 provides a nylon composite material, which is prepared using the same raw materials as in Example 1, and will not be described again.
[0189] The preparation method of the nylon composite material of Comparative Example 1 includes the following steps:
[0190] (1) Nylon 12, modified lubricant, antioxidant and continuous glass fiber are put into a mixer in proportion and mixed at a speed of 400 rpm, a temperature of 30℃ and a mixing time of 5 min to obtain a premix.
[0191] (2) The above premix is added through the main feed port of a twin-screw extruder, and then granulated after passing through the twin-screw extruder to prepare nylon composite material. In the nylon composite material, the continuous glass fibers are cut into smaller pieces than the length of the nylon composite material granules. The screw temperatures of the twin-screw extruder are 240℃, 280℃, 290℃, 300℃, 300℃, 290℃, 290℃, 280℃, 280℃, 280℃, and 280℃, and the rotation speed is 500 rpm.
[0192] After the nylon composite material of Comparative Example 1 was processed into a sample, its performance was tested according to the standard. The test results are shown in Table 2.
[0193] Comparative Example 2
[0194] Comparative Example 2 provides a nylon composite material whose raw materials are similar to those of Example 1, except that no modified lubricant is added; instead, it is added to nylon 12. Specifically, by mass percentage, the raw materials for the nylon composite material of Comparative Example 2 include: 69.6% nylon 12 PA12-1, 30% continuous glass fiber 4301R, 0.2% antioxidant 1010, and 0.2% antioxidant 168.
[0195] The preparation method of the nylon composite material in Comparative Example 2 is the same as that in Example 1, and will not be repeated here.
[0196] After the nylon composite material prepared in Comparative Example 2 was processed into samples, its performance was tested according to the same standard. The test results are shown in Table 2.
[0197] Comparative Example 3
[0198] Comparative Example 3 provides a nylon composite material, the raw materials of which are similar to those of Example 1, except that the modified lubricant in Example 1 is replaced with an unmodified lubricant, erucamide.
[0199] The preparation method of the nylon composite material in Comparative Example 3 is the same as that in Example 1, and will not be repeated here.
[0200] After the nylon composite material prepared in Comparative Example 3 was processed into samples, its performance was tested according to the same standard. The test results are shown in Table 2.
[0201] Comparative Example 4
[0202] Comparative Example 4 provides a nylon composite material, the raw materials of which are similar to those of Example 1, except that ordinary short glass fibers 992B are used instead of the continuous glass fibers in Example 1.
[0203] The preparation method of the nylon composite material in Comparative Example 4 is the same as that in Example 1, and will not be repeated here.
[0204] After the nylon composite material prepared in Comparative Example 4 was processed into samples, its performance was tested according to the same standard. The test results are shown in Table 2.
[0205] Comparative Example 5
[0206] Comparative Example 5 provides a nylon composite material, the raw materials of which are similar to those in Example 1, the difference being the modified lubricant. The modifier used in Comparative Example 5 is mercaptopropyltrimethoxysilane. Other aspects are the same as in Example 1 and will not be repeated.
[0207] The preparation method of the nylon composite material in Comparative Example 5 is the same as that in Example 1, and will not be repeated here.
[0208] After the nylon composite material prepared in Comparative Example 5 was processed into samples, its performance was tested according to the same standard. The test results are shown in Table 2.
[0209] Table 2 Performance test results of nylon composite materials from the examples and comparative examples
[0210]
[0211] The performance test results in Table 2 show that, compared with Comparative Examples 1-5, the nylon composite material prepared in this application exhibits higher strength, higher modulus, and higher impact resistance. Specifically, the comparison between Example 1 and Comparative Example 1 reveals that Comparative Example 1 uses a traditional process, mixing nylon, modified lubricant, continuous glass fiber, and antioxidant before extrusion granulation. The continuous glass fiber is shredded, resulting in a final nylon composite material with fiber lengths shorter than the nylon composite granule length, leading to significantly inferior performance compared to Example 1. In contrast, Example 1 involves mixing and extruding nylon, modified lubricant, and antioxidant into an impregnation mold, then feeding continuous glass fiber into the mold for mixing and impregnation with the premix, followed by traction and granulation. This results in a final nylon composite material where the glass fiber length is equal to the nylon composite granule length, resulting in superior strength, modulus, and impact resistance. The comparison between Example 1 and Comparative Examples 2, 3, and 5 shows that the nylon composite materials prepared without modified lubricant, or with a modified lubricant different from those in the examples of this application, exhibit significantly worse performance than those in Example 1. Furthermore, the comparison between Comparative Examples 2, 3, and 5 further reveals that the mechanical properties of Comparative Examples 3 and 5, which use small-molecule lubricants, are reduced compared to Comparative Example 2, which does not contain lubricant. However, the addition of lubricants from some embodiments of this application increases the molecular weight of the modified lubricant due to the Diels-Alder reaction between the cellulose groups at room temperature, thereby improving the mechanical properties of the material. The comparison between Example 1 and Comparative Example 4 shows that the nylon composite material prepared using short glass fibers as raw material in Comparative Example 4 exhibits poor performance.
[0212] The comparison of the examples also shows that as the amount of glass fiber in the nylon composite material increases, the strength, modulus, and impact resistance of the nylon composite material further increase. Furthermore, it should be noted that in Example 2, due to the lower amount of continuous glass fiber, its strength, modulus, and impact resistance are lower than those of the comparative examples based on Example 1. However, a comparison of Example 1 and Comparative Examples 1-5 suggests that, compared to Example 2, if no modified lubricant is added or the added lubricant differs from that in the examples of this application, its performance will be significantly lower than that of Example 2.
[0213] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0214] The embodiments described above are merely illustrative of several implementation methods of this application, intended to facilitate a detailed understanding of the technical solutions of this application, but should not be construed as limiting the scope of protection of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the scope of protection of this application. It should be understood that technical solutions obtained by those skilled in the art based on the technical solutions provided in this application through logical analysis, reasoning, or limited experimentation are all within the scope of protection of the appended claims. Therefore, the scope of protection of this patent application should be determined by the content of the appended claims, and the specification and drawings can be used to interpret the content of the claims.
Claims
1. A nylon composite material, characterized in that, The nylon composite material comprises, by weight percentage: 37%~89% nylon, 10%~60% long glass fiber, and 0.5%~3% modified lubricant; The length of the long glass fiber is equal to the length of the nylon composite material, and the modified lubricant includes a furfural-modified amide lubricant.
2. The nylon composite material according to claim 1, characterized in that, The raw materials for preparing the modified lubricant include: amide lubricant and modifier, wherein the amide lubricant includes one or both of erucamide and oleamide, and the modifier includes compounds containing mercapto and furfural groups; Optionally, the modifier includes one or both of 3-mercapto-furfuryl alcohol and furfuryl thiol.
3. The nylon composite material according to claim 2, characterized in that, The modified lubricant satisfies one or more of the following conditions: (1) The molar amount of thiol groups contained in the modifier is 100% to 200% of the molar amount of carbon-carbon double bonds contained in the amide lubricant; optionally, the molar amount of thiol groups contained in the modifier is 120% to 180% of the molar amount of carbon-carbon double bonds contained in the amide lubricant; (2) The raw materials for preparing the modified lubricant also include a photoinitiator, wherein the molar amount of the photoinitiator is 1% to 10% of the molar amount of the modified agent; Optionally, the molar amount of the photoinitiator is 2% to 6% of the molar amount of the modifier; Optionally, the photoinitiator includes one or both of 2,2-dimethoxy-2-phenylacetophenone and benzophenone.
4. The nylon composite material according to claim 1, characterized in that, The nylon includes one or more of nylon 12, nylon 11, and nylon 1012; and / or, Under test conditions of 190℃ and 2.16kg load, the melt index of the nylon is 3g / 10min~40g / 10min.
5. The nylon composite material according to claim 1, characterized in that, The long glass fiber includes alkali-free long glass fiber; optionally, the long glass fiber includes alkali-free long glass fiber modified with a coupling agent containing amino and / or epoxy groups.
6. The nylon composite material according to any one of claims 1 to 5, characterized in that, One or two of the following conditions must be met: (1) By weight percentage, the nylon composite material comprises: 50%~78% nylon, 20%~48.5% long glass fiber and 1%~2% modified lubricant; (2) The nylon composite material further includes 0.1% to 0.9% antioxidant; Optionally, the antioxidant includes one or both of antioxidant 1010 and antioxidant 168.
7. A method for preparing a nylon composite material, characterized in that, Includes the following steps: The following raw materials are obtained by weight percentage: 37%~89% nylon, 10%~60% continuous glass fiber, and 0.5%~3% modified lubricant; The raw materials are mixed and granulated so that the length of the granules is equal to the length of the continuous glass fibers after shearing, in order to prepare the nylon composite material. The modified lubricant includes a furfuryl-modified amide lubricant.
8. The method for preparing the nylon composite material according to claim 7, characterized in that, The steps of mixing and granulating the raw materials include: The nylon and the modified lubricant are mixed to prepare a premix; The premix is extruded and then injected into an impregnation mold; The continuous glass fiber is fed into the impregnation mold and mixed and impregnated with the premix. After traction and granulation, the nylon composite material is prepared. Optionally, the step of mixing the raw materials satisfies one or more of the following conditions: (1) In the step of mixing the nylon and the modified lubricant, the rotation speed is 50 rpm to 1000 rpm, the temperature is 0℃ to 60℃, and the time is 1 min to 10 min; optionally, the rotation speed is 150 rpm to 600 rpm, the temperature is 15 to 40℃, and the time is 3 min to 6 min. (2) In the step of extruding the premix, a twin-screw extruder is used, wherein the screw temperature of the twin-screw extruder is 220℃~300℃ and the rotation speed is 150rpm~900rpm; optionally, the screw temperature is 240℃~280℃ and the rotation speed is 300rpm~700rpm. (3) The temperature of the impregnation mold is 260℃~300℃, and optionally, the temperature of the impregnation mold is 270℃~290℃.
9. The method for preparing the nylon composite material according to claim 7 or 8, characterized in that, The modified lubricant is prepared by the following steps: An amide lubricant, a modifier, a photoinitiator, and a solvent are mixed, and the amide lubricant is reacted with the modifier under nitrogen protection and ultraviolet light irradiation to prepare the modified lubricant; wherein the amide lubricant includes one or both of erucamide and oleamide, and the modifier includes compounds containing thiol and furfuryl groups; Optionally, the preparation steps of the modified lubricant satisfy one or more of the following conditions: (1) The power of the ultraviolet lamp is 36W~72W and the ultraviolet wavelength is 200nm~360nm; optionally, the ultraviolet wavelength is 250nm~350nm; (2) The reaction time between the amide lubricant and the modifier is 10 min to 30 min and the temperature is 10℃ to 40℃; optionally, the reaction time is 15 min to 25 min and the temperature is 20℃ to 35℃.
10. The use of the nylon composite material as described in any one of claims 1 to 6 or the nylon composite material prepared by the preparation method of the nylon composite material as described in any one of claims 7 to 9 in the manufacture of mechanical cams or sports shoe soles.